Maximum Power Control and Optimization of Switched Reluctance Generators for Wind Turbines - Parla, Gokhan; Yıldırım, Merve; Özdemir, Mehmet (My University, 2023)
In this paper, a maximum power control and optimization of a 4-phase 8/6-pole Switched Reluctance Generator (SRG) are realized for a wind energy conversion system by using MATLAB/Simulink. Unlike conventional generators, using of the SRGs has increased in variable speed wind turbines due to important advantages such as lower copper losses, simple structure, flexible control, and a good performance in a wide speed range. However, since SRGs work with switching logic, their torque production is fluctuating and optimum turn-on/turn-off angles of the phases must be determined to work as a generator. Therefore, in this study, these angles are optimized based on the speed of the SRG and Maximum Power Point Tracking (MPPT) is realized. Besides, a voltage control is provided by keeping the DC bus voltage at the output of the system constant at the desired value with the help of a chopper controlled unloader. The results obtained from the optimized model for variable wind speed conditions are compared with that of the unoptimized model. It is observed that the SRGs can work more stable with a proper optimization method and the power obtained from the system follows the maximum output power.
Keywords: Optimization; maximum power point tracking; Asymmetric bridge type converter; switched reluctance generator; wind power plant